Relational attractiveness between supplier-customer in a supply chain - Santana, Rodrigo Soares; Salati Marcondes de Moraes, Gustavo Herminio; Ribeiro da Silva, Hermes Moretti [UNESP] (Univ Sao Paulo, Fac Economia, 2021)
Purpose - This study aims to evaluate the influence of factors attributed to relationship attractiveness between supplier and customer, from the supplier's perspective. Design/methodology/approach - The empirical exercise was based on the use of multivariate data analysis with confirmatory factor analysis and a partial least squares approach to structural equation modeling. Findings - The study resulted in a robust model, with a high explanatory factor for the latent variable relational attractiveness and commitment was the most influential factor, followed by expected value and interorganizational trust. Research limitations/implications - Some limitations of the study can be highlighted: conducting research in a single cooperative and with a single audience; choosing a short-cycle supply chain, which may make it difficult to generalize to other industries; the cross-section nature of data also hinders the analysis to understand how the association between variables of interest may vary over time. Practical implications - The negative influence of interpersonal trust reinforces the importance of developing collaborative attitudes between parties, whereas the non-significant value for dependence (financial and volume dependence) shows this is not a risk factor for relational attractiveness in a supply chain. Such results provide evidence on how to develop relationship management between suppliers and customers that are part of the same supply chain. Social implications - It offers a new perspective for research in cooperatives, which still have no consensus on the motivating factors for members' participation, including as evidence the results of the largest flower producing center in Latin America. The more a cooperative succeeds in increasing relational attractiveness, the greater the cooperative power and the ability to adapt to shocks and changes, which are fundamental factors for the success and longevity of the cooperative. Originality/value - The research presents a model that is comprehensive enough to fit in different contexts and consider its specific characteristics. Additionally, this paper has added in-depth information on the relational attractiveness relationships in the context of a developing country.
Keywords: Brazil; Relationship marketing; B2B relationship; Cooperativism; Relational attractiveness